2021
DOI: 10.3346/jkms.2021.36.e15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiovascular Risk Factors and Cardiovascular Diseases on Outcomes in Patients Hospitalized with COVID-19 in Daegu Metropolitan City

Abstract: Background: Data regarding the association between preexisting cardiovascular risk factors (CVRFs) and cardiovascular diseases (CVDs) and the outcomes of patients requiring hospitalization for coronavirus disease 2019 (COVID-19) are limited. Therefore, the aim of this study was to investigate the impact of preexisting CVRFs or CVDs on the outcomes of patients with COVID-19 hospitalized in a Korean healthcare system. Methods: Patients with COVID-19 admitted to 10 hospitals in Daegu Metropolitan City, Korea, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
(38 reference statements)
1
17
1
2
Order By: Relevance
“…Hypertension was more prevalent in hospitalised patients compared with those diagnosed with COVID-19 (range 25.6%–85.9% vs 17.4%–61.4%, respectively). The observed variability between databases is similar to previous reports, where the prevalence ranged from 28.8% 7 to 60%. 15 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hypertension was more prevalent in hospitalised patients compared with those diagnosed with COVID-19 (range 25.6%–85.9% vs 17.4%–61.4%, respectively). The observed variability between databases is similar to previous reports, where the prevalence ranged from 28.8% 7 to 60%. 15 …”
Section: Discussionsupporting
confidence: 90%
“…To date, observational studies, [4][5][6][7][8][9][10][11][12][13][14][15][16] systematic reviews and meta-analyses have reported an increased risk of progression to severe COVID-19 and increased mortality in patients with hypertension. [17][18][19][20][21] However, these studies either only included hospitalised patients, 4-13 15 16 leading to selection bias, or had a small sample size, 6-10 15 both of which limit extrapolation of results.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis performed among Iranian patients by Merjalili et al revealed that diabetes was associated with higher mortality, while arterial hypertension was not [ 26 ]. Park et al analyzed the Korean population and found both diabetes and hypertension to be risk factors for death in the course of COVID-19 [ 34 ]. The same results were achieved by Gupta et al among Indian patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…CVD and associated risk factors (adjOR = 1.79, P = 0.027), diabetes (OR = 2.43, P < 0.001), and congestive HF (OR = 2.43, P = 0.049) independently predicted in-hospital death. [ 67 ]…”
Section: Common Covid-19 Risk Factorsmentioning
confidence: 99%